Joint characterization of middle and low rank coal pores and fractures based on pressed mercury-nitrogen adsorption-nuclear magnetic resonance method - LIU Jiajia; ZHANG Yunlong; YANG Di; GAO Zhiyang; WANG Dan (河南理工大学学报. 自然科学版)
ObjectivesIn order to further study the pore structure and distribution of middle and low rank coal，Methodsmercury injection， low temperature liquid nitrogen adsorption and low field nuclear magnetic resonance experiments were used to jointly characterize the pore structure and pore size distribution of the low rank coal in Aiweilgou 1890 coal Mine （XJ） and the middle rank coal in Hebi No.8 Coal Mine （HB）， combined with fractal dimension. A full-aperture fractal dimension characterization method based on dominant interval is proposed， namely： the fractal dimension of r<140 nm is characterized by FHH model using liquid nitrogen method； The fractal dimension of aperture 140~1 000 nm was characterized by NMR model. The fractal dimension of aperture r>1 000 nm was characterized by the Menger sponge model of mercury injection method.ResultsThe results show that： The large and medium pores of low-rank XJ coal are mainly composed of open pores， and the small pores are mainly composed of closed and semi-closed pores. Among them， the contribution rate of large pores to pore volume is the highest， reaching more than 94%， and the contribution rate of medium pores is the main contributor of pore specific surface area， accounting for 40.58%. The small pores and medium pores are relatively developed， while the large pores are almost undeveloped， and the pore connectivity of small pores is poor. The connectivity of large pores is good. The pores of HB medium-rank coal are mainly composed of semi-closed pores， in which the proportion of large pores is the highest， accounting for more than 97% of the pore volume. The specific surface area of pores is mainly contributed by small pores， with a contribution rate of 58.33%. Small pores are mainly developed， while medium pores， large pores or cracks are relatively undeveloped， and the pore connectivity is poor. The DFT model of liquid nitrogen method shows that the most developed pore diameter of low-rank XJ coal is 10~12 nm， and that of mid-rank HB coal is 1~4 nm. The fractal dimension of HB mid-rank coal is significantly larger than that of XJ low-rank coal in the r<140 nm pore size range， and the heterogeneity of HB mid-rank coal is stronger than that of XJ low-rank coal in this pore size range， and the pore structure is more complex. The fractal dimension of the mid-rank coal of HB is smaller than that of the low-rank coal of XJ in the pore size range of r>140 nm， and the pore structure of the low-rank coal of XJ is more complex than that of the mid-rank coal of HB.ConclusionsResearch achievements provides theoretical guidance for the fracture expansion and gas migration in the middle and low-rank coal seam.